Effect of sintering aids on the grain growth of simulated dupic fuel pellets using the simfuel technique. Issue 1 (January 2016) - Lee, Jae-Won; Jeon, Sang-Chae; Kang, Sang-Jun; Lee, Ju-Ho; Cho, Yung-Zun; Park, Geun-Il; Lee, Jung-Won
Abstract: The effect of sintering aids on the grain growth of simulated DUPIC fuel pellets with burn-ups was investigated using SIMFUEL pellets as a surrogate for actual spent PWR fuel avoiding the high radioactivity of spent fuel. In this study, titania and niobia were used as sintering aids, and SIMFUEL pellets with burn-ups of 35 GWd/tU and 60 GWd/tU were used. The sintering aids significantly improved the grain sizes of the sintered pellets. Moreover, metallic precipitates, which inhibit the movement of the grain boundary, were included even at the interior of grains due to an increase of grain boundary mobility caused by the addition of sintering aids. Titania is more effective than niobia in grain growth, while niobia is more effective than titania in densification.